Performance psychology with military personnel, law enforcement officers, and firefighters: A systematic review of research on mental qualities and techniques - Castillo, Elmer; Raabe, Johannes; Carl, Johannes (Association for Applied Sport Psychology's (AASP) 2020 Annual Conference, 2020)
While applied sport psychology services have traditionally been provided in athletic settings, there has been a trend towards a more general application across different performance domains (Gould, 2002) and, in particular, with tactical populations (i.e., military, law enforcement, and firefighters; e.g., Zinsser, Perkins, Gervais, & Burbelo, 2004). For mental performance consultants who work with military personnel, law enforcement officers, and firefighters, it is valuable to consistently reflect on clients’ cognition, affect, and behavior from a scientific perspective to inform their practice (Jones & Mehr, 2007). Accordingly, the purpose of the current study was to systematically review the existing research on mental qualities and techniques in tactical populations. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (Moher, Liberti, Tetzlaff, & Altman, 2009). After searching relevant databases and removing duplicates, 6,883 potentially pertinent articles were found. These were subsequently screened by two independent reviewers based on predefined inclusion criteria. This systematic screening process helped to identify 36 relevant articles that were retained for further analysis. In those included studies, researchers provided information regarding the antecedents, mediators, and consequences of 12 different mental qualities and techniques, along with 40 other variables. Overall, the reviewed findings highlight the benefits of developing mental qualities and techniques among military personnel, law enforcement officers, and firefighters as they have been shown to nurture a range of positive cognitive, affective, and behavioral outcomes (e.g., less anxiety, higher well-being, and better performance). Nevertheless, the review also highlights limitations (e.g., sample size) that need to be addressed in future research to gain a more comprehensive understand ing of these psychological constructs. This presentation will provide empirical evidence to inform the delivery of applied performance psychology to tactical populations and allow for an effective use of the scientist-practitioner approach to service provision.